Caracterización estructural de un bosque de Podocarpus parlatorei y Juglans australis en Salta, Argentina - Pinazo, Martín Alcides (2003)
Stands of Subtropical Montane Cloud Forest were studied in areas under different land use regimes near Los Toldos (NW Argentina). Circular plots were used to calculate density and basal area of trees with dbh > 10 cm; and density of trees with dbh < 10 cm. The stands were classified and grouped as a function of basal area. Five structures were recognized, with different proportions of Juglans australis, Podocarpus parlatorei and shade-tolerant species like Blepharocalyx salicifolius, Allophylus edulis and Myrcianthes sp. Less disturbed area stands had a higher basal area and greater dbh for all species, and shade-tolerant species in the canopy. In the most disturbed area, all canopy species were shade intolerant and regeneration was dominated by shade-tolerant species. The differences in composition, basal area, stem diameter class distribution and regeneration indicate that the structure types corresponded to different stages of the successional process, and the regeneration of the most disturbed areas suggest a tendency towards the composition of mature forest.